THE EFFECT OF FERMENTED RICE WASHING WATER AND VINEGAR SOAKING ON THE SHELF LIFE OF RED TILAPIA FILLETS DURING LOW-TEMPERATURE STORAGE BASED ON ORGANOLEPTIC CHARACTERISTICS - Luther, Abraham; Liviawaty, Evi; Haetami, Kiki (Jurnal Perikanan Unram, 2025)
Red Nile tilapia (Oreochromis niloticus) fillet is a highly nutritious aquaculture product but is prone to spoilage, thus requiring environmentally friendly preservation innovations. This study aimed to evaluate the effect of fermented rice washing water with varying vinegar concentrations on the organoleptic characteristics of red tilapia fillets during cold storage. The research was conducted experimentally at the Laboratory of Fishery Product Technology, Universitas Padjadjaran, using five vinegar concentration treatments (0%, 0.5%, 1%, 1.5%, and 2%), and organoleptic parameters observed included appearance, odor, mucus, and texture. Data were analyzed using the Friedman test and Bayesian analysis. The results showed that the treatments significantly affected fillet shelf life, particularly in maintaining appearance and mucus up to day 11 of storage. The 1% vinegar concentration was identified as the most effective treatment in preserving fillet freshness during refrigeration. In general, the combination of fermented rice washing water and vinegar can serve as a natural preservative alternative to extend the shelf life of fishery products.